The first two mitochondrial genomes from Apiotrichum reveal mitochondrial evolution and different taxonomic assignment of Trichosporonales - Qiang Li; Wenqi Xiao; Peng Wu; Ting Zhang; Peng Xiang; Qian Wu; Liang Zou; Mingying Gui (IMA Fungus)
Abstract Apiotrichum is a diverse anamorphic basidiomycetous yeast genus, and its mitogenome characterization has not been revealed. In this study, we assembled two Apiotrichum mitogenomes and compared them with mitogenomes from Agaricomycotina, Pucciniomycotina and Ustilaginomycotina. The mitogenomes of Apiotrichum gracile and A. gamsii comprised circular DNA molecules, with sizes of 34,648 bp and 38,096 bp, respectively. Intronic regions were found contributed the most to the size expansion of A. gamsii mitogenome. Comparative mitogenomic analysis revealed that 6.85–38.89% of nucleotides varied between tRNAs shared by the two Apiotrichum mitogenomes. The GC content of all core PCGs in A. gamsii was lower than that of A. gracile, with an average low value of 4.97%. The rps3 gene differentiated the most among Agaricomycotina, Pucciniomycotina and Ustilaginomycotina species, while nad4L gene was the most conserved in evolution. The Ka/Ks values for cob and rps3 genes were > 1, indicating the two genes may be subjected to positive selection in Agaricomycotina, Pucciniomycotina and Ustilaginomycotina. Frequent intron loss/gain events and potential intron transfer events have been detected in evolution of Agaricomycotina, Pucciniomycotina and Ustilaginomycotina. We further detected large-scale gene rearrangements between the 19 mitogenomes from Agaricomycotina, Pucciniomycotina and Ustilaginomycotina, and fifteen of the 17 mitochondrial genes shared by Apiotrichum varied in gene arrangements. Phylogenetic analyses based on maximum likelihood and Bayesian inference methods using a combined mitochondrial gene dataset revealed different taxonomic assignment of two Apiotrichum species, wherein A. gamsii had a more closely relationship with Trichosporon asahii. This study served as the first report on mitogenomes from the genus Apiotrichum, which promotes the understanding of evolution, genomics, and phylogeny of Apiotrichum.